2019
DOI: 10.1017/s0263034619000442
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the electron acceleration in vacuum by chirped ultrashort laser pulse using particle swarm method

Abstract: Efficient electron acceleration by a linearly chirped ultrashort laser pulse in vacuum is investigated using the particle swarm optimization method. By applying this method for optimizing the initial parameters of the laser pulse, a pronounced increase in final energy gain of the electron is obtained compared to that expected from the successive optimization method. Our results also suggest that the value of the optimal chirp parameter is independent of laser polarization and the energy gain could be insensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…[13][14][15][16][17] Many studies, experiments, and simulations have proposed to increase the wakefield amplitude and electron acceleration. [18][19][20][21][22][23] A plasma beat wave accelerator (PBWA) without the need for high-power lasers was one of the first ideas to be proposed. 4,24,25 The modulation of laser beams is associated with beating two laser pulses with slightly different wavelengths focused in plasma and creating a longitudinal ponderomotive force.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Many studies, experiments, and simulations have proposed to increase the wakefield amplitude and electron acceleration. [18][19][20][21][22][23] A plasma beat wave accelerator (PBWA) without the need for high-power lasers was one of the first ideas to be proposed. 4,24,25 The modulation of laser beams is associated with beating two laser pulses with slightly different wavelengths focused in plasma and creating a longitudinal ponderomotive force.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of frequency chirp has been considered in many cases such as studies on particle acceleration, wakefield generation and terahertz radiation. [34][35][36][37][38] Zhang et al, [34] studied the variation of the chirped 800-nm pulse duration in both experiment and simulation. They revealed that there is the optimum chirp to maximize the THz yield so that extremely sensitive to the temporal propagation.…”
Section: Introductionmentioning
confidence: 99%